A legal review on the Malaysian judges' code or ethic / Muhammad Yazid Mohamad Salim…[et al.] - Mohamad Salim, Muhammad Yazid; Abdul Aziz, Ahmad Lokman; Yusof, Nor Azhari; Othman, Haziq (2010)
The basic idea behind this research project paper is to identify several issues. The first one will be on the purpose of the establishment of the Judges' Code of Ethic 1994 and the problems within the 1994 Code itself which render it to be difficult in term of enforcement. Secondly, to look through the new Judges' Code of Ethic 2009 which had replaced the 1994 code, whether or not this new code had solved all the problems faced by the Judges' Code of Ethic 1994. In our findings, it was proven that the 1994 code do have several problems as well as lacuna which also can be the main cause why it has not been used or referred. Comparatively, eventhough the new 2009 Code of Ethic had covered some of these problems, the new code itself do still have problems which need to be looked into. This project paper manages to compare Malaysia Judges' Code of Ethic with the Judges' Code of Ethic from other countries such as India, Australia and United States. In order to make this particular Judges' Code of Ethic workable and implementable, we have gathered some recommendations and suggestions from people who are expert in relation to this matter. In conclusion, all the problems and lacuna identified under the 1994 and 2009 Judges' Code of Ethic need to be considered and reviewed so that we can came out with a more comprehensive and absolute Code of Ethic for the judges.